IMPLEMENTATION OF HALAL TOURISM IN INCREASING INTEREST IN VISITING TOURISTS FROM WEST SUMATRA - Wenisarahmi Alfin; Aldri Frinaldi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The aim of this research is analyze the application of halal tourism in attracting tourist visits to West Sumatra. The method used in this study is qualitative with a descriptive approach. Data was collected through interviews, observation and documentation. To verify the validity of the data, source triangulation techniques were used, and data analysis was carried out through data reduction, data presentation, and drawing conclusions. The policy implementation model applied in this research refers to G. Shabbir Cheema and Dennis A. Rondinelli, who highlight factors such as environmental conditions, inter-institutional relationships, organizational resources in program implementation, as well as the characteristics and capabilities of implementing agents. Based on research findings, it shows that the implementation of halal tourism in West Sumatra is quite successful and able to increase tourist interest. However, there are still several challenges, such as inadequate accommodation, lack of available facilities, and permit procedures that are not yet optimal.